Monthly girls' Nozaki-kun. 13 - Tsubaki, Izumi (Yen Press, 2022)
"Secret after secret among Nozaki and friends is revealed, plunging the groupeven further into chaos! Who exactly owns the rather unique books in Nozaki's closet? What does Sakiko Yumeno do in her (his) free time? Will Wakamatsu ever actually figure out who Lorelai really is...?!!"--Back cover